Congenital heart disease in spondylothoracic dysostosis: two familial cases. Issue 8 (August 1995) - Simpson, J M; Cook, A; Fagg, N L; MacLachlan, N A; Sharland, G K
Abstract : Two familial cases of spondylothoracic dysostosis are reported. Both cases had severe congenital heart disease in addition to the skeletal malformations which are characteristic of the condition.